El manejo de cargas y su incidencia en la salud laboral de los trabajadores de la empresa TRIBOILGAS en el año 2012. Propuesta de un programa de protección y músculo - esquelético. - Coronel Basurto, Mario Xavier (2015)
The company TRIBOILGAS in an oil services company, whose main business is to oil drilling and workover identifying risks in cargo handling is a major risk, morbidity presented in the company, states that injuries musculoskeletal disorders occupies 31%, of which the jobs with the highest incidence with these injuries accounted for keyways and Encuelladores, this incidence led to prepare this study ergonomic evaluation, with the aim of implementing a program Prevention of skeletal muscle injury to reduce musculoskeletal disorders. A descriptive field research, the study unit was 15 company employees TRIBOILGAS, including in positions of worker yard, keyway, encuellador and machinist, the instrument of the research was the Nordic questionnaire that was identified was made that the since most at risk was the keyway, and the muscle group most affected is back in the position of machinist it was found that their conditions were the result of their activities in their previous positions as a method of verification methods used ergonomic evaluation, REBA, RULA, OWAS and G-INSHT, where it is confirmed that the level of risk in these positions and activities is very high, resulting in high morbidity lumbar therefore raised the proposal after the study establishes, reduce risk, train staff on issues of cargo handling, performing procedures and protocols in the health of workers.